385 A Cell Resolution Atlas of the Human Cerebrovasculature Reveals Angiogenic and Inflammatory Cell Programs in Arteriovenous Malformations. (April 2023) - Winkler, Ethan A.; Kim, Chang; Ross, Jayden; Garcia, Joseph; Gil, Eugene; Oh, Irene; Chen, Lindsay; Wu, David; Catapano, Joshua; Raygor, Kunal P.; Narsinh, Kazim; Kim, Helen; et al.
Abstract : INTRODUCTION: Coordinated communications between multiple cell types is responsible for cerebrovascular structure and function. Cellular dysfunction results in cerebrovascular diseases, a leading cause of death and disability. However, we lack a complete census of human cerebrovascular cells necessary to advance understanding of disease mechanisms and therapeutic strategies. METHODS: To provide a human cerebrovascular cell atlas, we used single-cell RNA sequencing (scRNAseq) to molecularly profile dissociated vascular cells isolated from the adult human brain and AVMs. Joint comparative analyses profiled patterns of aberrant gene expression in AVMs and resolved cell states enriched in AVMs that bled. Results were validated with fluorescent in situ hybridization, immunostaining, and in vitro functional assays RESULTS: By performing scRNAseq on 181, 388 single-cells, we identified > 40 molecularly-defined vascular or neighboring cell states from the human cerebrovasculature and AVMs. We identified endothelial molecular signatures underlying arteriovenous phenotypic changes known as "zonations." Our study uncovered an expanded diversity of perivascular cells unique to humans. In AVMs, there was a loss of normal arteriovenous molecular patterning characterized by the emergence of an endothelial cell state with heightened angiogenic potential and immune cell cross-talk within the AVM nidus. We characterized the cellular ontology of cerebrovascular-derived immune cell response and identified infiltration of distinct immune cell states, such as GPNMB+ monocytes, which deplete stabilizing smooth muscle cells in AVMs that bled. CONCLUSIONS: Our single-cell atlas highlighted the heterogeneity underlying cell function and interaction in the human cerebrovasculature and defined molecular and cellular perturbations in AVMs, a leading cause of stroke in young people. The identified interplay between vascular and immune cells will aid development of therapeutics targeting angiogenic and inflammatory programs in vascular malformations.